Apremilast in Patients With Active Rheumatoid Arthritis: A Phase II, Multicenter, Randomized, Double‐Blind, Placebo‐Controlled, Parallel‐Group Study. Issue 7 (July 2015) - Genovese, Mark C.; Jarosova, Katerina; Cieślak, Dorota; Alper, Jeffrey; Kivitz, Alan; Hough, Douglas R.; Maes, Peter; Pineda, Lilia; Chen, Mindy; Zaidi, Farrukh
<x xml:space="preserve">Abstract</x> Objective To study the efficacy/safety of apremilast, an oral phosphodiesterase 4 inhibitor, compared with placebo in patients with active rheumatoid arthritis (RA) who had an inadequate response to methotrexate (MTX). Methods Patients were randomized 1:1:1 to receive placebo, apremilast 20 mg twice a day, or apremilast 30 mg twice a day. Patients whose swollen and tender joint counts had not improved by ≥20% were considered nonresponders at week 16 and were required to enter the protocol‐defined early escape. At week 24, patients were transitioned in a blinded manner to receive apremilast 20 mg twice a day if they were initially randomized to receive placebo. Patients who were not initially randomized to receive placebo continued to receive their target apremilast dose. Patients were required to take a stable dose of MTX (7.5–25 mg/week) throughout the study. Magnetic resonance imaging (MRI) was performed in a subset of patients. Results A total of 237 patients who were receiving MTX therapy were randomized and received ≥1 dose of study medication. At week 16, similar proportions of patients receiving placebo (35%), apremilast 20 mg twice a day (28%), and apremilast 30 mg twice a day (34%) met the American College of Rheumatology criteria for 20% improvement in disease activity (the primary efficacy end point). In the MRI substudy, mean change from baseline in total joint damage scores according to the Rheumatoid Arthritis Magnetic Resonance Imaging Scoring system was generally similar with either apremilast dose at week 16. At week 52, no trends were noted for clinical end points by treatment group. Both apremilast doses were generally well tolerated. Conclusion Apremilast efficacy was not demonstrated in patients who had active RA despite stable MTX therapy.